The impact of penalties on attack frequency in high-level judo matches - Ceylan, B.; Balci, S. S.; Taskin, H. B.; Santos, L. (International Journal of Performance Analysis in Sport, 2023)
This study aimed to determine the effect of penalties on attack frequency in high-level judo matches. The study investigated 194 matches (74 women`s and 120 men`s matches) where at least one of the two competitors received the second shido. The penalties affected the attack frequency (F2, 360 = 30.81, p < 0.001). The attack frequency was the highest after the second shido, while it was the lowest before athletes were penalised with the first shido. The increase in nage-waza attack frequency increased the possibility of winning a match twice (odds ratio (OR) = 2.01), and the increase in the number of ne-waza attacks per minute increased the possibility of winning a match 3 times (OR = 3.13). Moreover, the increase in the attack frequency especially following the second shido significantly increased the possibility of winning compared to previous penalties (OR = 1.13). Thus, the current study concludes that penalties affect match dynamics, and the change in the number and frequency of attacks affects match outcome. It is suggested that athletes should perform positive activities to increase the possibility of winning. Coaches could plan tactical trainings by taking the number of penalties into account.